The landing error scoring system (LESS) is a valid and reliable clinical assessment tool of jump-landing biomechanics - Padua, D. A.; Marshall, S. W.; Boling, M. C.; Thigpen, C. A.; Garrett, W. E.; Beutler, A. I. (The American Journal of Medical Sciences, 2009)
Anterior cruciate ligament injuries are common in athletes and have serious sequelae. A valid clinical tool that reliably identifies individuals at an increased risk for ACL injury would be highly useful for screening sports teams, because individuals identified as "high-risk" could then be provided with intensive prevention programs.